ADAKAH PERBEDAAN STATUS GIZI ANTARA REMAJA SANTRIWATI YANG BERPUASA DAN TIDAK BERPUASA SENIN KAMIS ? (Studi di Pondok Pesantren Al Itqon Semarang) - Desy Kustiyanti; Suyatno Suyatno; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The purpose of this study was to analyze the differences in nutritional status between Monday – Thursday fasting and not fasting adolescent female students. This study used an observational design with a cross - sectional approach. The population of this study was 235 students. Among them, 27 female adolescent students who fasted regularly and 100 female adolescent students who did not fast regularly were included as the subjects in this study. Data were collected through interviews by 2 x 24 hours food recall method and the measurements of weight, height and percent body fat. Data analysis used Independent t-test and Mann-Whitney test. The results showed that there was no difference in BMI Z- scores between the Monday-Thursday fasting (0.09 ± 1.25)kg/m2 and non fasting female adolescents (-0.13 ± 1.35) kg/m2 ,with a p-value of 0.440.There was no difference in percent body fat between the fasting (25,84 ± 6,00)% and not fasting (25,03 ± 5,86)% female adolescent students, with a p-value of 0.527. On the fasting day, the average energy adequacy level in the fasting group (52.45 ± 9.10) %, was lower than the non fasting group (77.87 ± 23.01)%, with a p-value of 0.0001.The average protein adequacy level in the fasting group (44.95 ± 13.37)%, was lower than the non fasting group (64.55 ± 25.38)%, with a p-value of 0.0001, but the fat adequacy level in the fasting group (131,53 ± 54,88) was higher than the non fasting groups, with a p-value 0.0001. It is concluded that the nutritional status of adolescent females who fasted was similar to those who were not fasted, although the energy and protein consumption was higher in the non fasting group.